Preventive Measures for Adolescent Traffic Accidents Through Safety Vehicle Extension Activities - Budi Mardikawati; Putu Eka Suartawan; Hendrik Prasetyo; A.A Bagus Oka Khrisna Surya; Stefanus Sylvan Rianto; Aswin Badarudin Atmajaya (Politeknik Trasportasi darat Bali, 2022)
The increase in transportation needs has an impact on increasing the number of accidents, which are dominated by human error factors. Preventive measures are needed to prevent traffic violations. The purpose of this activity is to provide counseling to high school students about safe vehicles. The method used in the activity is direct counseling with discussion and question and answer methods. The target of this activity is the 54 students of SMA Negeri 1 Kediri, Tabanan-Bali. The material presented consists of 4 parts, namely: 1) driving preparation; 2) Driving Attitude; 3) Rules on the Highway; and 4) traffic violations. In addition to the presentation of the material using the question and answer method, quizzes were also given as material for further discussion. The results obtained by the students looked enthusiastic and able to learn well. This can be seen from the increase in the average value of the Pre-Test to the Post-Test value. Improved understanding of driving well, is expected to increase awareness and discipline of students in driving so as to reduce the number of traffic accidents by teenagers.